Підвищення ефективності утилізації теплоти когенераційних газопаротурбінних установок з термосифонними котлами-утилізаторами = Increase in efficiency of heat recovery exhaust gases of cogeneration combined-cycle power plants with thermosyphon heat-recovery boilers - Долганов, Ю. А.; Dolganov, Yu. A. (My University, 2015)
Дисертація присвячена дослідженню актуальної науково-технічної проблеми – підвищенню ефективності утилізації теплоти когенераційних газопаротурбінних установок з термосифонними котлами-утилізаторами. У дисертації наведені огляд та аналіз сучасних схемних рішень когенераційних ГПТУ з термосифонними котлами-утилізаторами. Удосконалено математичну модель розрахунку теплових схем когенераційних ГПТУ, яка забезпечує визначення раціональних параметрів робочого тіла теплоутилізаційного контуру з урахуванням змінних протягом року температур зовнішнього повітря, конструктивні особливості водотрубних КУ, та на відміну від існуючих, додатково враховує конструктивні особливості термосифонних секційних котлів-утилізаторів і їх вплив на електричну, теплову потужність та узагальнюючі показники надійності установки. Запропоновано програмне забезпечення для проведення автоматизованих розрахунків на ЕОМ. Проведено експериментальні дослідження внутрішнього температурного перепаду двохфазних гравітаційних термосифонів в діапазоні теплових навантажень від 0,5 до 17 кВт/м2, в результаті яких отримана залежність tтс = f (qтс) для розрахунку внутрішнього температурного перепаду в порожнині термосифонів. Вдосконалена конструкція та метод теплового розрахунку термосифонного секційного котла-утилізатора горизонтальної компоновки з природною циркуляцією у випарному контурі. Підвищення ефективності утилізації теплоти когенераційних газопаротурбінних установок з термосифонними котлами-утилізаторами досягнуто за рахунок зростання теплової потужності відповідних поверхонь нагріву внаслідок збільшення площі теплообміну. = The dissertation is devoted to actual scientific and technical problems – improve the efficiency of heat recovery cogeneration combined cycles power plants with thermosyphon recovery boilers. The thesis provides a review and analysis of modern circuit design cogeneration combined cycles power plants with thermosyphon heat recovery boilers. Improved mathematical model calculation of schemes cogeneration combined cycles power plants which additionally takes into account the structural features of thermosyphon sectional recovery boilers and their effect on the electrical, thermal capacity and reliability generalizing installation. Carried out the experimental investigations of the internal temperature gradient gravitational two-phase thermosyphon heat loads ranging from 0.5 to 17 kW/m2, which resulted in the dependence tts = f (qts) to calculate the internal temperature gradient in the cavity thermosyphon. An improved method for calculating the thermal sectional thermosyphon heat recovery boilers, by taking into account the additional internal temperature gradient in thermosyphon that served to clarify the heat transfer coefficients in the boiler heating surfaces. Performing thermal calculations of cogeneration combined cycles power plants with UGT6000 showed that by taking into account tts managed to get the growth of thermal power to 157 kW (about 6% of the total) and electric power to 149 kW (about 2% of the total) by increasing the respective heating surfaces. Increase in electrical efficiency was 1.3% and the utilization rate of heat fuel 1.4%. Specific fuel consumption per 1 kW of electric power decreased by 4%. Improving the efficiency of heat recovery of cogeneration combined cycle power plants with thermosyphon heat recovery boilers achieved by increasing the heat output to the heating surfaces due to increased heat transfer area.
Долганов, Ю. А. Підвищення ефективності утилізації теплоти когенераційних газопаротурбінних установок з термосифонними котлами-утилізаторами : автореф. дис. ... канд. техн. наук : 05.05.03 / Ю. А. Долганов ; МОН України, НУК ім. адмірала Макарова ; наук. керівник О. А. Єпіфанов. – Миколаїв, 2015. – 20 с.
Keywords: газопаротурбінна установка; когенерація; котел-утилізатор; термосифон; combined-cycle power plants; cogeneration; heat-recovery boiler; thermosyphon